2003
DOI: 10.1080/10473289.2003.10466229
|View full text |Cite
|
Sign up to set email alerts
|

Day-of-Week Patterns of Particulate Matter and Its Chemical Components at Selected Sites in California

Abstract: This paper analyzes day-of-week variations in concentrations of particulate matter (PM) in California. Because volatile organic compounds (VOCs) and oxides of nitrogen (NO x ) are not only precursors of ozone (O 3 ) but also of secondary PM, it is useful to know whether the variations by day of week in these precursors are also evident in PM data. Concentrations of PM Յ10 m (PM 10 ) and Յ2.5 m in aerodynamic diameter (PM 2.5 ) were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 14 publications
4
20
0
1
Order By: Relevance
“…This is probably caused both by the emissions and the chemistry of SO 2 . Emissions of SO 2 from power plants decline by 5 to 15% on weekends compared to weekdays, a much smaller change than the approximately 75% reduction in diesel emissions on weekends in California (Chinkin et al, 2003;Motallebi et al, 2003). Electric power generation accounted for about 70% of US SO 2 emissions during the period 2000-2006 (National Emissions Inventory (NEI) Air Pollutant Emissions Trends Data, http://www.epa.gov/ ttn/chief/trends/index.html).…”
Section: Sulfate and Nitratementioning
confidence: 99%
See 1 more Smart Citation
“…This is probably caused both by the emissions and the chemistry of SO 2 . Emissions of SO 2 from power plants decline by 5 to 15% on weekends compared to weekdays, a much smaller change than the approximately 75% reduction in diesel emissions on weekends in California (Chinkin et al, 2003;Motallebi et al, 2003). Electric power generation accounted for about 70% of US SO 2 emissions during the period 2000-2006 (National Emissions Inventory (NEI) Air Pollutant Emissions Trends Data, http://www.epa.gov/ ttn/chief/trends/index.html).…”
Section: Sulfate and Nitratementioning
confidence: 99%
“…Almeida et al (2006) found that chemical elements such as Ca, Si, and Fe associated with soil were significantly higher on weekdays at a site in a suburb of Lisbon. Motallebi et al (2003) found weekly cycles at selected urban sites in California. Lough et al (2006) and Harley et al (2005) found significant weekly trends in aerosol components in the Los Angeles area.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest the potential for near-field impacts from strong sources such as ship plumes. Day-of-the-week differences in PM mass concentrations have been routinely observed where motor vehicle traffic is the dominant source of PM (Motabelli et al 2003;Aalto et al 2005; among others). We observe similar differences in the number concentration at the selected study sites representative of the overall study ( Figure 6, Table 3, Figures S8-S9).…”
Section: Total Particle Number Concentrationsmentioning
confidence: 99%
“…Uncertainties for the EC and OC data were not reported. Norris et al (2014) suggested that, for such cases, the initial uncertainties be set to a proportion of the concentration. The uncertainties for OC and EC were therefore calculated as 10 % of the corresponding concentrations for this study.…”
Section: Positive Matrix Factorization Analysismentioning
confidence: 99%